2018
DOI: 10.1016/j.triboint.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Friction scale effect in drilling natural fiber composites

Abstract: This work aims to investigate the multiscale tribological behavior when drilling natural fiber composites by changing the tool-composite interface trough the modification of the tool coating. Drilling experiments were carried out on bidirectional flax fibers reinforced polypropylene resin using the same drilling tool geometry with three different coating properties. Results show that the tribo-mechanical behavior of the drilling operation is affected by changing the tool coating at different scale levels. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Figures 6 and 7 show that the specific cutting energy for the thrust force decreased with an increase in feed rate, but increased when the spindle speed increased. This result is in agreement with the literature [11]. It is also observed that an increase in the drill's diameter contributes to a decrease of the specific cutting energy for the thrust force ( Figure 6).…”
Section: Specific Cutting Energy For Thrust Forcesupporting
confidence: 93%
See 1 more Smart Citation
“…Figures 6 and 7 show that the specific cutting energy for the thrust force decreased with an increase in feed rate, but increased when the spindle speed increased. This result is in agreement with the literature [11]. It is also observed that an increase in the drill's diameter contributes to a decrease of the specific cutting energy for the thrust force ( Figure 6).…”
Section: Specific Cutting Energy For Thrust Forcesupporting
confidence: 93%
“…Venkateshwaran and ElayaPerumal [10] presented that an increase in the feed rate and the spindle speed contributed to the rise of the delamination factor during drilling of epoxy composite reinforced with banana fibers. Chegdani and Mansori [11] found that the use of coated tools generated an increase in specific cutting energy in the drilling of bidirectional flax fiber reinforced polypropylene. The study [12] explored the machinability of two types of green composites (Sisal/PLA and Grewia Optiva/PLA).…”
Section: Introductionmentioning
confidence: 99%
“…Friction is a complex phenomenon that cannot be reduced to a single mechanism, but rather is a result of a simultaneous action of various mechanisms at different hierarchy and scale levels [30,31]. To understand this specific friction behavior of the two NFRP constituents, Fig.…”
Section: Friction Properties By Scratch Testmentioning
confidence: 99%
“…In recent years, natural fibers such pineapple, flax, jute, coconut, sugarcane bagasse, palm, and others have been extensively studied as an alternative to reinforce polymer matrix due to their advantages such as sustainable, low cost, low density and biodegradable features [1][2][3]. However, the incompatibility with nonpolar matrices, moisture adsorption and vulnerability to thermal degradation are the main disadvantages for the use of natural fibers in composites [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%